Exploring risk and protective factors which distinguish suicidal and self-harm behaviours from suicidal and self-harm ideation in young people: A systematic review - Marianne E. Etherson; Sieun Lee; Krystyna J. Loney; Isobel P. Steward; Joey Ward; Heather McClelland; Aaron Kandola; Josimar A. De Alcantara Mendes; Chris Hollis; Ellen Townsend; Dorothee P. Auer; Rory C. O’Connor (PLoS ONE, 2025)
Background Self-harm and suicidal thoughts and behaviours among young people are significant global public health concerns. Although most young people with thoughts of self-harm or suicide do not act on their thoughts, it is important to identify factors that distinguish thoughts of self-harm and suicide from behaviours. To date, there are no reviews distinguishing self-harm and suicidal behaviours from thoughts of self-harm and suicide in young people or that have synthesised factors distinguishing self-harm behaviours from self-harm ideation. The current review addresses these gaps in the literature. Methods We systematically searched: CINAHL, Embase, Medline, PsycINFO, Psychology and Behavioural Sciences Collection, and Web of Science Core Collection for articles published between 2011 and April 2024. Ninety-nine studies met inclusion criteria, with 92 articles examining risk and protective factors that distinguished suicide attempts from suicidal ideation and seven articles examining factors that distinguished self-harm behaviours from self-harm ideation. Using a narrative synthesis approach, studies were grouped by their outcome variable (e.g., self-harm or suicide) and then by risk and protective factors. Results While findings were inconsistent, the presence of non-suicidal self-injury, physical, emotional, or sexual abuse, violence, and family factors (e.g., family conflict) distinguished suicidal attempts from suicidal ideation. By contrast, the presence of parental factors (e.g., parental connectedness) and greater academic achievement were protective and distinguished suicidal ideation from suicide attempts. Being female, exposure to self-harm/suicide, and impulsivity distinguished self-harm behaviours from self-harm ideation. There was no evidence of protective factors that distinguished self-harm behaviours from self-harm ideation. Conclusions The current review highlights important risk and protective factors that distinguish suicidal and self-harm behaviours from suicidal and self-harm ideation in young people. Our review has important implications for intervention and prevention efforts as identifying key risk and protective factors can improve risk assessment for young people experiencing thoughts of self-harm and suicide and enable more targeted interventions.